Inclusive innovation processes in Tanzania: From national policies to local practices in innovation hubs - Hooli, Lauri; Nkonoki, Emma; Leppänen, Ville (Taylor & Francis, 2025)
Inclusive innovations have the potential to foster socio-economic development and actively involve local communities in innovation processes in Sub-Saharan Africa. The importance of inclusive innovations is emphasized in the public strategies and development programs in the region. Nevertheless, despite some donor-funded initiatives, there remains a lack of systematic knowledge on how to effectively implement inclusive innovation in communities. This research aims to scrutinize the role of inclusive innovation in Tanzania. We conduct policy analyses of the country's official innovation strategies and investigate the inclusive innovation activities undertaken by 12 innovation hubs. These hubs facilitate interactions among diverse actors, provide necessary facilities and technologies, and offer mentorship and peer support. Our results reveal that the definition and significance of inclusive innovation are presented within the national policies. However, implementation programs are currently modest and scattered. With a few exceptions, innovation hubs have inadequate understanding and limited resources for implementing inclusive innovations in practice. This research contributes by underscoring the need for comprehensive strategies, capacity-building initiatives, and collaborative efforts to fully leverage inclusive innovation for sustainable development in the region.